Guidelines for conducting an appropriate curriculum vitae - Kelesi-Stavropoulou, Martha; Fasoi, Georgia (Health & Research Journal, 2015)
When searching for a job, the composition of a properly formulated Curriculum Vitae (CV) is particularly important. The CV is the key element of evaluation from the side of businesses. It describes concisely and accurately all the individual knowledge, experiences and skills which were acquired both in education and in his professional career. The goal of the CV is to stimulate the interest and attention of future employers and to convince them for the suitability of the candidate in a specific position. A properly formulated CV is often cited as the most appropriate way of advertising oneself. Although there isn’t a strict reporting methodology in drafting a CV, the literature describes points which should be followed, and others which should be avoided, so that it clearly demonstrates the ability of the candidate for a job through the description of qualifications. Also specific sections of the CV are described which should always focus on what is requested by an enterprise. The ultimate goal is the information relating to the person described in such a way as to demonstrate that it excels against fellow candidate for the position.